The Effect of Ethanoic Extract of Tetrapleuratetraptera (Uyayak) on Pain Sensitivity of Female Wistar Rats (International Journal of Physiology, 2024)
Background: In African traditional medicine, the dried pods of Tetrapleura tetraptera are frequently used tomanage different human ailments. In Nigeria, it is consumed in soups after childbirth to aid in wound healing,pain relief, uterine recovery, and lactation. The study investigates the impact of Tetrapleura tetraptera fruit extracton pain sensitivity using Wistar rats.Methods: Twelve female Wistar rats were divided into two groups (Group 1 - Control and Group 2 -100mg/kg Tetrapleura tetraptera extract-fed) and received standard rat chow and water for fourteen days followingwhich pain sensitivity was assessed using a hot plate. The results were presented as Mean and IndependentStudent T-test was utilized for statistical analysis with significance determined at P≤0.05. Increased pain toleranceindicated reduced sensitivity.The escape latencies of both groups were 5secs and 10secs respectively. Group 2 demonstrated a noteworthyincrease in pain tolerance compared to Group 1 (P < 0.05). analgesic This experimental study indicates that theethanoic extract of Tetrapleura tetraptera fruit has properties.Conclusion: The result of this study provides support for the use of dried Tetrapleura tetraptera pods in painmanagement across some communities in Southern Nigeria.